Design a Low-Cost Digital Pressure Meter Equipped with Temperature and Humidity Parameters - Utomo, Bedjo; Hariwisana, I Dewa Gede; Misra, Shubhrojit (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2021)
Calibration is a technical activity which consists of determining one or more properties and characteristics of a product, process or service according to a predetermined special procedure. The purpose of calibration is to ensure measurement results comply with national and international standards. The purpose of this study is to design two mode digital pressure meter (DPM) device equipped with a thermo-hygrometer and pressure in which the design is completed with a selection mode to determine the positive and negative pressure (vacuum) using MPX 5050GP sensor as a positive pressure sensor. In this design DHT 22 sensors is used to measure the humidity and temperature. To test the leak test this device is also equipped with timer. This design uses a 2.4 inch Nextion TFT LCD screen to display data. Data analysis was performed by comparing modul with standard tools. In the measurement process, Mercury tensimeter was carried out 6 times the data and the smallest results were 0 mmHg on the module and 0 mmHg on the standard tool and the largest was 298.0 mmHg on the module and 300 mmHg on the standard tool. Data were collected in a room with a temperature of 31̊C and humidity of 87%. Finally, this design is applicable for daily used for electromedical engineer to calibrate the sphygmomanometer in the hospitals